Além dos limites: Explorando a sustentabilidade do novo regime fiscal (2019 - 2022) - Andrade, Mayk Rodrigues de (2024)
The dissertation "Beyond Limits: Exploring the Sustainability of the New Fiscal Regime (2019- 2022) critically addresses the implementation and consequences of the New Fiscal Regime (NRF), established by Constitutional Amendment 95/2016 during the Temer administration, currently considered the main fiscal anchor in Brazil. Its creation aimed at controlling spending by the Union, in response to the persistent scenario of fiscal deficits being recorded. The policy is criticized for potentially limiting investments in sectors strategic for socio-economic development and for ignoring the needs arising from demographic and social changes. The overall objective of this dissertation is to highlight the infeasibility of the New Fiscal Regime, as it imposes excessively rigid and unrealistic limits on the budgetary demands of the Brazilian State. Methodologically, the study is supported by bibliographic research, documentary analysis, and data analysis. From a theoretical perspective, the effectiveness of fiscal policies is discussed through the analysis of economic theories, contrasting the view of expansionary austerity with Keynesian and post-Keynesian approaches to substantiate criticism of the NRF. The results of this research demonstrate that the adopted fiscal regime imposes overly strict and unrealistic constraints on the growth of public expenditure, proving unworkable in the face of the Brazilian State's budgetary reality. In the empirical analysis, the five episodes of "loopholes" in the spending ceiling are investigated, including the Onerous Assignment, Capitalization of non-dependent state-owned enterprises, the War Budget, Precatórios, and the Kamikaze Constitutional Amendment, demonstrating through detailed analysis of policies and constitutional amendments, the impracticability of the NRF. The study questions the long-term sustainability of the NRF and suggests the need for its revision in light of the complex social and economic demands faced by the country.